Tray efficiency effects in batch distillation - Ukeje-Eloagu, Chibuike Igbokwe (1998)
Computer simulation has long been recognised as a useful tool in improved process operation and design studies. Commercial simulation packages now available for batch distillation studies typically assume constant tray efficiency. Here, on the basis of both practical work and computer simulation, the effects of tray efficiency variation with tray liquid composition on model accuracy and column performance are investigated.